Pemanfaatan Data Satelit Himawari-8 dalam Analisis Kejadian Hujan Lebat di Jombang - Wahyu Sulistiyono; Miranda Sahfira Tuna; Shandy Alhaq Ramadhan (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2024)
On February 2, 2021, flooding struck Jombang, damaging 38 houses and public facilities due to heavy rainfall from cumulonimbus clouds. The analysis of convective cloud development using Himawari-8 Satellite with RGB Day Convective Storm, 24H-Microphysics, Airmass, and Cloud Convective Overlay methods revealed that the microphysics phase occurred in two different phases on February 1 and 2. The peak temperature of the Cb cloud during the development phase ranged from -20 to -60°C. Convective cloud clusters originated from the Java Sea and the Southern Sea. The peak cloud formation occurred at 12:00 UTC on February 1 and 2. Increased updraft and thickness intensity strengthened convective cloud formation. During the decay phase, downdraft increased with a decrease in cloud distribution, as observed in the Day Convective Storm and 24H-Microphysics images.